Does heat acclimation improve exercise capacity at altitude? A cross-tolerance model - White, A. C.; Salgado, R. M.; Schneider, S.; Loeppky, J. A.; Astorino, T. A.; Mermier, C. M. (International Journal of Sports Medicine, 2014)
New approaches to inducing altitude acclimation in a relatively short timeframe are needed, as it is not practical for many soldiers and athletes to gain access to specialized training facilities. Acclimation to one environmental stressor could enhance adaptation to various other stressors in animals and humans. This phenomenon has been described as cross-tolerance and involves the activation of common protective pathways. The purpose of this review is to discuss possible mechanisms involved in the cross-tolerance between heat and hypoxia. Future data could potentially support the use of a cross-tolerance model as a means for military personnel to prepare for deployment to high-altitude environments, as well as for athletes competing at high altitude.